2005
DOI: 10.1164/rccm.200408-998oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypocapnic but Not Metabolic Alkalosis Impairs Alveolar Fluid Reabsorption

Abstract: Acid-base disturbances, such as metabolic or respiratory alkalosis, are relatively common in critically ill patients. We examined the effects of alkalosis (hypocapnic or metabolic alkalosis) on alveolar fluid reabsorption in the isolated and continuously perfused rat lung model. We found that alveolar fluid reabsorption after 1 hour was impaired by low levels of CO 2 partial pressure (PCO 2 ; 10 and 20 mm Hg) independent of pH levels (7.7 or 7.4). In addition, PCO 2 higher than 30 mm Hg or metabolic alkalosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…In agreement with these latter studies, we found that ventilation at 18 cmH 2 O P results in an increase in amiloride-sensitive, CFTR inh -172-sensitive AFC that can be blocked by adenosine deaminase and an A 2b -AdoR inhibitor and mimicked in mice ventilated at 10 cmH 2 O P with exogenous adenosine. Adenosine appears to be the primary mediator of AFC enhancement at high P. Potential roles for endogenous catecholamines (27), alterations of bronchoalveolar PCO 2 (3,30), or atelectrauma (17) as mediators of responses to P were all excluded in our studies. While confirmation of our proposed mechanism will require further experiments in AdoR-knockout mice, the data presented herein provide further support for the concept that adenosine acts as a central regulator of lung fluid balance, as recently proposed by Factor et al (12) and Kreindler and Shapiro (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these latter studies, we found that ventilation at 18 cmH 2 O P results in an increase in amiloride-sensitive, CFTR inh -172-sensitive AFC that can be blocked by adenosine deaminase and an A 2b -AdoR inhibitor and mimicked in mice ventilated at 10 cmH 2 O P with exogenous adenosine. Adenosine appears to be the primary mediator of AFC enhancement at high P. Potential roles for endogenous catecholamines (27), alterations of bronchoalveolar PCO 2 (3,30), or atelectrauma (17) as mediators of responses to P were all excluded in our studies. While confirmation of our proposed mechanism will require further experiments in AdoR-knockout mice, the data presented herein provide further support for the concept that adenosine acts as a central regulator of lung fluid balance, as recently proposed by Factor et al (12) and Kreindler and Shapiro (22).…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the higher basal AFC rate at 18 cmH 2 O P is also a consequence of upregulated CFTR inh -172-sensitive AFC (Cl Ϫ absorption via CFTR). ␤-agonists have been shown to increase AFC in normal and injured lungs (27), whereas both hypercapnia (PCO 2 of 60 mmHg) (3) and hypocapnia (PCO 2 Յ 20 mmHg) (30) have been shown to inhibit AFC. However, increasing P from 10 to 18 cmH 2 O had no effect on either plasma epinephrine levels (63 Ϯ 3 pg/ml and 60 Ϯ 2 pg/ml, respectively; n ϭ 8) or plasma norepinephrine levels (810 Ϯ 71 pg/ml and 840 Ϯ 48 pg/ml, respectively; n ϭ 8), which were measured at the end of the 30-min ventilation period, and which did not differ significantly from those in unventilated mice.…”
Section: Effect Of P On Basal Afc Rate In Balb/c Micementioning
confidence: 99%
“…Hypoxia reduces alveolar epithelial sodium and fl uid reabsorption by downregulation of apical Na + -K + ATPase and basolateral epithelial sodium channels ( ENaC ) and this may play a role in the development of HAPE [ 28 , 171 ]. Respiratory alkalosis may impair alveolar fl uid reabsorption [ 98 ] by reversible downregulation of basolateral membrane Na + -K + ATPase abundance. In addition, alkalosis may also impair ENaC gating leading to less sodium fl ux across the apical membrane [ 30 ].…”
Section: Hypoxia and Respiratory Alkalosis At High Altitudementioning
confidence: 99%
“…and then injected with insulin. The isolated lung preparation has been previously described (Briva et al, 2007;Myrianthefs et al, 2005;Rutschman et al, 1993;Saldias et al, 2001). Briefly, the lungs and heart were removed en bloc.…”
Section: Isolated Perfused Rat Lung Modelmentioning
confidence: 99%